If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -25 = 87 + -8x Solving -25 = 87 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -25 + 8x = 87 + -8x + 8x Combine like terms: -8x + 8x = 0 -25 + 8x = 87 + 0 -25 + 8x = 87 Add '25' to each side of the equation. -25 + 25 + 8x = 87 + 25 Combine like terms: -25 + 25 = 0 0 + 8x = 87 + 25 8x = 87 + 25 Combine like terms: 87 + 25 = 112 8x = 112 Divide each side by '8'. x = 14 Simplifying x = 14
| (3x^2+2x)+(3x^2-2x)= | | f(x)=2x-4graph | | 3(x+4)-x=24+x | | t-2=-3t+4 | | Y-8=-1(x+12) | | 1/3*2/5=34 | | 60=3x-2y | | 3(-1)+4(-1+3)=5 | | 3x+2x-4x+5x=18 | | 5x+15=-45 | | 7u=43.75 | | Y-8=-2(x+3) | | 8w=25.6 | | 3x+4(x+3)=5 | | (4x+8)-(6x-8)= | | 7x+61=40 | | (13m^4+2)+(m^4n^2+2-2m^4)-(-13m^2n^3+5m^4)= | | 10z-5+32=8-2 | | (8+x)(8+y)=169 | | 21-36= | | 2/3w-3=9 | | f(x)=-24 | | 4m+7-2m-5= | | 4x+4=6x+2 | | (8+x)(8+y)=164 | | N-26=-50 | | f(x)=-12 | | x+36=-40 | | 7-2x=-21 | | y+1.5=7.9 | | 10x+15y=425 | | u=(2u^2-u+4)+(-5u^2+3u+6) |